2020
DOI: 10.3390/pr8070804
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Lactoferrin Isolated from Acid Whey Using Pilot-Scale Monolithic Ion-Exchange Chromatography

Abstract: The aim of this study was to characterize the properties of lactoferrin (LF) obtained in a process developed for its isolation from acid whey derived from the production of fresh curd cheese, using a unique technology of ion-exchange chromatography on CIM® monolithic columns. The freeze-dried lactoferrin samples produced on the pilot plant (capacity 1 m3) were examined for the purity, iron-binding capacity, antibacterial activity, and pH- and temperature-stability. Apo-LF inhibited several tested strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
1
23
1
Order By: Relevance
“…The Arrhenius equation was linear in the temperature range from 60 to 80 • C. However, the rate constant at 50 • C significantly deviated from the correlation (Figure 4) indicating changes in the degradation mechanism of Lf between 50 and 60 • C. Our findings are following results obtained by other researchers who used the same Lf isolate samples to study the thermodynamic stability by UV-VIS spectroscopy. It was found that Lf is thermally stable up to about 53 • C with a denaturation temperature of 58.6 • C [21]. The activation energy calculated from the Arrhenius plot was found to be 78.4 kJ/mol, which is lower than values found in the literature.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The Arrhenius equation was linear in the temperature range from 60 to 80 • C. However, the rate constant at 50 • C significantly deviated from the correlation (Figure 4) indicating changes in the degradation mechanism of Lf between 50 and 60 • C. Our findings are following results obtained by other researchers who used the same Lf isolate samples to study the thermodynamic stability by UV-VIS spectroscopy. It was found that Lf is thermally stable up to about 53 • C with a denaturation temperature of 58.6 • C [21]. The activation energy calculated from the Arrhenius plot was found to be 78.4 kJ/mol, which is lower than values found in the literature.…”
Section: Discussioncontrasting
confidence: 59%
“…High purity Milli-Q water was obtained through a Milli-Q A10 Advantage water purification system (Millipore Corporation, Bedford, MA, USA). Different lots of solid Lf isolate samples (1–3; A-value of 3.4–5.2% [ 21 ]), as well as liquid Lf isolate samples (elutions E1, E3, and concentrated E3) were obtained from ARHEL d.o.o. (Ljubljana, Slovenia).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no bacteriostatic effect was observed on Lactobacillus acidophilus. Matijašic et al, (2020) examined the antimicrobial effects of seven different lactoferrins isolated from whey and produced in the pilot plant by the disk diffusion method. Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, Salmonella enterica, Clostridium difficile, Klebsiella oxytoca, and Clostridium perfringens were selected as potentially pathogenic indicator bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Lactoperoxidase and lysozyme are the most abundant antimicrobial enzymes in milk, while lactoferrin is the most abundant antimicrobial peptide (Yılmaz and Tosun, 2012). Antimicrobial proteins and peptides are produced by the secretory fluids produced by many organisms as a primary defense mechanism (Matijašic et al, 2020).…”
Section: Introductionmentioning
confidence: 99%